Improved Wielandt method with real-time error tolerance based on NLSP3 code. (March 2023) - Pan, Qingquan; Cai, Yun; Wang, Lianjie; Liu, Xiaojing; He, Hui; Wang, Kan
Highlights: Innovation: two formulas (Eq. (34) and Eq. (40)) are established for the first time; Universality: can be easily applied by a variety of deterministic codes; Feasibility: tested by the 2D-IAEA benchmark and the 3D-IAEA benchmark; Significance: effectively improves the efficiency of the Wielandt method. Abstract: The Wielandt method reduces the number of outer iterations but increases the number of inner iterations. The number of calculated inner iterations should be reduced to improve the efficiency of the Wielandt method, and then the error tolerance for the Wielandt inner iteration should be larger. We give a new formula to calculate the error tolerance and achieve the real-time adjustment of the error tolerance for the Wielandt inner iteration. The improved Wielandt method is implemented in NLSP3 code, and tested by the 2D-IAEA benchmark and the 3D-IAEA benchmark. The results show that the improved Wielandt method can reduce the total number of calculated inner iterations, thus improving the efficiency of the Wielandt method.